# algebra

posted by .

Use the method of substitution to solve the system.
xy=1
4x-y+3=0

• algebra -

xy = 1,
4x - y + 3 = 0.

Solve 1st Eq for x:
X = 1/y,

Substitute 1/y for x in EQ2:
4/y - y + 3 = 0,
Multiply both sides by -y:
-4 + y^2 - 3y = 0,
y^2 - 3y - 4 = 0,
Factor the trinomial:
(y + 1) (y - 4) = 0,
y + 1 = 0,
y = -1.

y - 4 = 0,
y = 4.

Substitute -1 for y in Eq1:
x*-1 = 1,
x = -1.

Substitute 4 for y in Eq1:
x * 4 = 1,
x = 1/4.

Solution set: (-1 , -1) , (1/4 , 4).

## Similar Questions

1. ### Substitution Method-Plz help

Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get it.How …
2. ### algebra

how do you use the substitution method to solve the linear system?
3. ### algebra

Requesting help. (I must reckon, that X is a variable, and y is y-intercept) Q: Try to use the substitution method to solve the the linear system y=3x an y=3x-7. What do you notice?
4. ### Algebra

-3x + 2y = 8 x + 4y = -4 use substitution method to solve the linear system.
5. ### algebra

use method of substitution to solve the system of linear equation 3x+4y=3/2 y=2x-1
6. ### algebra

Use the substitution method to solve the linear system. Thanks! s= t+4 2t+s=19
7. ### Algebra

Use the substitution method to solve the linear system. 1/8p+3/4q=7 3/2p-q=4 Thanks.
8. ### Algebra II

If you were to use the substitution method to solve the following system, choose the new system of equations that would result if x was isolated in the third equation. 2x - 3y + z = -4 2x - 2y + z = -1 x - 2y + 3z = -6 5x + 7y = 6 …
9. ### Algebra 1

bobpursey, In this problem you helped me with earlier: Solve using any appropriate method. y = 2× - 5, y = ½× + 1 Substitution, substitute for y. 2×-5=½ × + 1 3/2 x=6 x=4 y= 2*4-5=3 How did you choose which method you were going …